2014
DOI: 10.2753/ree1540-496x500308
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Private Benefits and Overinvestment

Abstract: According to agency theory, we hypothesize that underpayment of top management motivates management to overinvest. Using a sample of Chinese-listed companies for the period 2005-10, we assess the effect of managerial compensation on overinvestment and the effect of overinvestment on managerial private benefits, including future compensation and perquisites, as well as on firm performance. We find that underpayment does motivate overinvestment, which increases managerial private benefits but not firm value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
0
11
0
4
Order By: Relevance
“…Studies examining the effect of compensation on managers' decision and behavior still show a mixed result. Some researchers provided evidences of the alignment effect of compensation (Lei et al, 2014;Baxamusa, 2012;Broussard, Buchenroth, & Pilotte, 2004), but some others demonstrated an entrenchment effect where compensation actually motivates managers to take action which is not in line with the interests of shareholders (Baxamusa, 2012;Aggarwal & Samwick, 2006). We argue that this mixed result might be due to two reasons, the compensation effect on managerial decision and behavior might be contextual in nature.…”
Section: The Effect Of Compensation and Religiosity On Managers' Csr mentioning
confidence: 73%
“…Studies examining the effect of compensation on managers' decision and behavior still show a mixed result. Some researchers provided evidences of the alignment effect of compensation (Lei et al, 2014;Baxamusa, 2012;Broussard, Buchenroth, & Pilotte, 2004), but some others demonstrated an entrenchment effect where compensation actually motivates managers to take action which is not in line with the interests of shareholders (Baxamusa, 2012;Aggarwal & Samwick, 2006). We argue that this mixed result might be due to two reasons, the compensation effect on managerial decision and behavior might be contextual in nature.…”
Section: The Effect Of Compensation and Religiosity On Managers' Csr mentioning
confidence: 73%
“…Based on Richardson (2006), and following subsequent studies such as Goh et al (2016), Lei et al (2014), Liu and Bredin (2010), Huang et al (2015), and Zhang and Su (2015), we propose to use model (1) as a means to estimate firms’ level of overinvestment: where INEW i,t is new investment form firm i in year t , scaled by total assets. This variable depends on the lagged new investment (INEW t -1 ); the firm's growth opportunities (BM) measured as the book value of equity and liabilities divided by the sum of equity market value and book value of liabilities 2 ; the firm's leverage (LEV t -1 ) measured as the book value of total debt deflated by the sum of book value of total debt and the book value of equity; the firm's cash balance (CASH t -1 ); the log of the number of years the firm has been listed (AGE t- 1 ); the log of a firm's total assets (SIZE t -1 ); and the firm's stock returns (STOCKRETURN t -1 ).…”
Section: Model and Variablesmentioning
confidence: 99%
“…2Although different to that of Richardson (2006), this measure has been used in a number of recent studies (Di Meo, 2014; Lei et al, 2014; Lin, 2017; Ling et al, 2016; Shen et al, 2015) that also follow Richardson's model. Note that same as in Richardson (2006) the relation between the BM variable and a firm's growth opportunities is negative.…”
Section: Model and Variablesmentioning
confidence: 99%
See 2 more Smart Citations